Tasawuf sebagai Pendidikan Alternatif di Pesantren Anak: Studi Kasus Pondok Pesantren Miftahul Ulum Desa Glagahwero Kecamatan Kalisat Kabupaten Jember - Rizal, Syariful; Lutfi, Muhammad (Tasamuh: Jurnal Studi Islam, 2021)
National education in the Reformation Era is directed at achieving certain goals as stated in Law Number 20 of 2003 concerning SISDIKNAS, that "national education aims to educate the nation's life and develop Indonesian people as a whole. Islamic education as a sub-system of the national education system aspires to the formation of a complete Muslim, namely a qualified Indonesian Muslim while maintaining the noble culture of the nation. Thus education leads to the achievement of noble and harmonious values ​​for Muslim life which is characterized by Indonesia. However, in its journey, morality becomes just adab or manners, losing its philosophical substance; The morality of Indonesian Muslims is experiencing a crisis of morality, and ritual piety is often not positively correlated with social piety. The role of pesantren is needed through alternative education in the form of Sufism, because the science of Sufism can improve morality, as evidence of the success of pesantren in educating their students by integrating Sufism into daily life, so that the morals of students really increase as morality. Based on this, this research was carried out with a focus on How Sufism is an Alternative for Islamic Boarding School Education in Improving Santri Morals to God, Others, and the Environment at Miftahul Ulum Islamic Boarding School, Glagahwero Village, Kalisat District, Jember Regency. This research is a qualitative research. The results showed that, Sufism as an alternative to Islamic boarding school education in improving students' morals to Allah SWT, students' morals to others and students' morals to the environment, is a complex form of education that exceeds non-Islamic boarding school education with Sufism as an alternative education. In this case, the science of Sufism is taught through the recitation of the yellow books, through the practice of morality, and through practices in the form of tariqat/wiridan that are accustomed to every time. As a result, the science of Sufism as an alternative pesantren education taught at the Miftahul Ulum Glagahwero Islamic Boarding School, Kalisat District, Jember Regency has led students to have more moral character than before applying Sufism as an alternative pesantren education.